Antitumor effect of fibrin glue containing temozolomide against malignant glioma. Issue 5 (19th April 2014) - Anai, Shigeo; Hide, Takuichiro; Takezaki, Tatsuya; Kuroda, Jun‐ichiro; Shinojima, Naoki; Makino, Keishi; Nakamura, Hideo; Yano, Shigetoshi; Kuratsu, Jun‐ichi
<x xml:space="preserve">Abstract</x> Temozolomide (TMZ), used to treat glioblastoma and malignant glioma, induces autophagy, apoptosis and senescence in cancer cells. We investigated fibrin glue (FG) as a drug delivery system for the local administration of high‐concentration TMZ aimed at preventing glioma recurrence. Our high‐power liquid chromatography studies indicated that FG containing TMZ (TMZ‐FG) manifested a sustained drug release potential. We prepared a subcutaneous tumor model by injecting groups of mice with three malignant glioma cell lines and examined the antitumor effect of TMZ‐FG. We estimated the tumor volume and performed immunostaining and immunoblotting using antibodies to Ki‐67, cleaved caspase 3, LC3 and p16. When FG sheets containing TMZ (TMZ‐FGS) were inserted beneath the tumors, their growth was significantly suppressed. In mice treated with peroral TMZ plus TMZ‐FGS the tumors tended to be smaller than in mice whose tumors were treated with TMZ‐FGS or peroral TMZ alone. The TMZ‐FGS induced autophagy, apoptosis and senescence in subcutaneous glioma tumor cells. To assess the safety of TMZ‐FG for normal brain, we placed it directly on the brain of living mice and stained tissue sections obtained in the acute and chronic phase immunohistochemically. In both phases, TMZ‐FG failed to severely damage normal brain tissue. TMZ‐FG may represent a safe new drug delivery system with sustained drug release potential to treat malignant glioma.